Development and effectiveness of educational module on pre-pregnancy care among women of reproductive age with diabetes in Terengganu - Fauzi, Tengku Muhammad Fakhruddin Tengku Md (2024)
Background: Diabetes Mellitus (DM) stands as one of the major global health challenges of the twenty-first century. When DM is not well-managed, marked by maternal hyperglycaemia before and during the early stages of pregnancy, it significantly increases the risk of severe complications for both the mother and the developing foetus. Pre-Pregnancy Care (PPC) is particularly crucial for mothers with diabetes, as it provides substantial benefits to both the mother and the developing foetus. Objective: To develop and assess the effectiveness of the Educational Module on Pre-Pregnancy Care Among women of reproductive age with diabetes in Terengganu. Methodology: This study was structured in two primary phases: The first phase involved conducting a needs assessment, developing the educational module, and validating it. The second phase was a quasi-experimental study aimed at evaluating the module's effectiveness. The module's development followed the ADDIE model and included five stages: 1) Needs Assessment (A) 2) Consulting Experts for Module Design (D) 3) Post-Development Validation of the Educational Module for Pre-Pregnancy Care in women of reproductive age with diabetes (D), and 4) Implementing PPC Health Education. The quasi-experimental phase involved 90 diabetic women of reproductive age, with 45 in the intervention group from Dungun and 45 in the control group from Kuala Nerus, selected via simple random sampling. The intervention group utilized the newly developed module (I). The effectiveness of the module is determined through data analysis, encompassing improvements in knowledge and attitudes regarding PPC using Repeated Measures Analysis of Variance (RM-ANOVA) (E). Result: Focus Group Discussions (FGDs) was employed to assess needs and found four main themes: knowledge-related needs, attitude-related needs, health service-related needs, and perception-related needs. The module, divided into five units, covers the impact of diabetes on mothers and babies, the importance of PPC for diabetic mothers, PPC components, benefits of contraception, and maintaining controlled diabetes for the safety of both mother and baby. Experts assessed its content validity (S-CVI) as 1.0 and face validity as 0.99. There were significant changes in knowledge scores over time (F (1,88) = 76.87, p < 0.001), with a notable difference between the intervention and control groups in mean knowledge scores (F (1,88) = 5.71, p < 0.019) and a significant interaction effect (F (1,88) = 210.32, p < 0.001). Attitude scores also showed significant overall changes within groups over time (F (1,88) = 71.31, p < 0.001), with a significant mean score difference between groups regardless of time (F (1,88) = 67.47, p < 0.001) and a notable group-time interaction (F (1,88) = 127.81, p = 0.042). Conclusion: The study in Terengganu identified a significant need for a Pre-Pregnancy Care (PPC) educational module tailored for diabetic women of reproductive age, motivated by their desire for a healthy pregnancy. The developed module, validated for both reliability and relevance, effectively improved knowledge and attitudes towards PPC among the intervention group, as demonstrated by the quasi-experimental study's results.